2016
DOI: 10.2737/rmrs-gtr-346
|View full text |Cite
|
Sign up to set email alerts
|

Classification and description of world formation types

Abstract: An ecological vegetation classification approach has been developed in which a combination of vegetation attributes (physiognomy, structure, and floristics) and their response to ecological and biogeographic factors are used as the basis for classifying vegetation types. This approach can help support international, national, and subnational classification efforts. The classification structure was largely developed by the Hierarchy Revisions Working Group (HRWG), which contained members from across the America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 71 publications
(40 reference statements)
0
14
0
1
Order By: Relevance
“…With respect to the IVC hierarchy, E. tetrodonta woodlands in northern Australia highlight the differences in existing definitions of savanna (Fox et al 2001;Lehmann et al 2011;Dixon et al 2014) of at least >10% cover (Dixon et al 2014;Faber-Langendoen et al 2016). Although the E. tetrodonta woodlands predominantly have <40% tree cover (69% of plots) and a largely graminoid-or herbaceous-dominated ground layer (90% of plots; median cover = 37.2), they are consistently >8 m tall (97% of plots), include stands which are >40% tree cover (28% of plots), may include more than one structural layer (Addicott et al 2018b), and may have a sparse herbaceous ground layer <10% cover (16% of plots) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the IVC hierarchy, E. tetrodonta woodlands in northern Australia highlight the differences in existing definitions of savanna (Fox et al 2001;Lehmann et al 2011;Dixon et al 2014) of at least >10% cover (Dixon et al 2014;Faber-Langendoen et al 2016). Although the E. tetrodonta woodlands predominantly have <40% tree cover (69% of plots) and a largely graminoid-or herbaceous-dominated ground layer (90% of plots; median cover = 37.2), they are consistently >8 m tall (97% of plots), include stands which are >40% tree cover (28% of plots), may include more than one structural layer (Addicott et al 2018b), and may have a sparse herbaceous ground layer <10% cover (16% of plots) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Grasslands are classified into five types (Table 1). Following the International Vegetation Classification (Faber‐Langendoen et al, 2016) and Dixon et al (2014), four different grassland types were classified, namely, tropical grasslands, Mediterranean grasslands, temperate grasslands, and semidesert grasslands. In addition, grassland types that were unspecified in the primary studies were categorized as “grasslands unspecified” (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Although many abiotic and biotic variables can influence or moderate fire effects, we recorded how the authors described four common variables of interest: plant species composition, climate, topography, and soils for each study. We reviewed whether the plant species composition was reported using quantitative metrics (e.g., cover, tree density, and basal area), a qualitative description (i.e., plant list, plant associations, and habitat type), a cover type (e.g., Society of American Foresters; Eyre, 1980), or a physiognomic description (e.g., Faber-Langendoen et al, 2016). For climate, we noted whether studies reported a long-term climate average or a climate zone for their burn units.…”
Section: Methodsmentioning
confidence: 99%